Factors contributing to late stillbirth among women with pregnancy hypertension in a developing country - Manisha Kumar; Ravi Vajala; PhunstokDoma Bhutia; Abha Singh (Taylor & Francis Group, 2020)
Objective To investigate the factors associated with late stillbirth among women with hypertensive disorders of pregnancy (HDP). Material and Methods The clinical details of women with HDP having late stillbirth were compared with controls having livebirth. Results Total 208 cases and 288 controls were included in the study. Inadequate antenatal visits (p < 0.001, OR-5.92). birth weight < 2000 gms (p < 0.001, OR 10.3) and BW/PW ratio > 8 contributed significantly (p = 0.0001, OR-5.6) to stillbirth. Conclusion Poor antenatal care, birth weight below 2000gms and high BW/PW ratio was associated with a higher risk of stillbirth.